Prervation and cataloging serials (Anmol Pubications, 2001)
Contents of material: 1/ Preservation policies. 2/ Serials format. 3/ Origin of serial. 4/ Collection management. 5/ Periodicals listing. 6/ Study of periodical use. 7/ Journal ranking studies. 8/ Classification. 9/ Serials processing.